2014
DOI: 10.1016/j.joca.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

BMP activation and Wnt-signalling affect biochemistry and functional biomechanical properties of cartilage tissue engineering constructs

Abstract: While Wnt-activation is less effective, BMP-4/-7 heterodimer stimulation approximated native cartilage features in less than 50% of standard culture time representing a promising strategy for functional cartilage TE to improve biomechanical parameters of engineered cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…As such, the sGAG production and proliferation on the construct surface may be caused by the greater exposure of nutrients from the culture medium. This result has been seen in a previous porcine chondrocyte seeded collagen scaffold grown with growth factors . In this porcine study histology images revealed early sGAG production was concentrated on the scaffold surface.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As such, the sGAG production and proliferation on the construct surface may be caused by the greater exposure of nutrients from the culture medium. This result has been seen in a previous porcine chondrocyte seeded collagen scaffold grown with growth factors . In this porcine study histology images revealed early sGAG production was concentrated on the scaffold surface.…”
Section: Discussionsupporting
confidence: 85%
“…Tissue engineered studies using human articular chondrocytes grown in vitro produced compressive values about 50% of native tissue . In contrast, previous studies using animal derived chondrocytes (porcine, bovine, and canine) have shown compressive properties that range from 14 to 90% of native cartilage . The incorporation of growth factors and mechanical stimulation is known to enhance cartilage production and contributes to the improved compressive properties seen in some of these studies .…”
Section: Discussionmentioning
confidence: 97%
“…Although BMP-4/7 heterodimer strongly stimulated cartilage matrix deposition in chondrocytes in a previous study21, BMP-4/7 heterodimer neither enhanced proteoglycan deposition in MSC-derived pellets relative to TGF-β alone (Fig. 5a,b), nor did it stimulate collagen type II and/or collagen type X deposition in day 42 pellets according to Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…β-catenin accumulation activates transcription in conjunction with co-transcription factors, LEFs/TCFs [32]. It was previously reported that LiCl (5–10 mM) can effectively induce the canonical Wnt signaling pathway and mediate cell differentiation of MSCs [16,17,33] and articular chondrocytes [34]. SB216763 has been shown to regulate cell proliferation and survival and to induce the transcription of β-catenin-dependent genes [24].…”
Section: Discussionmentioning
confidence: 99%